RANCANGAN MEDIA POSTER PENGARUH PEMBERIAN AIR KELAPA MUDA TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica chinensis L) DENGAN SISTEM HIDROPONIK WICK PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN SMA KELAS XII - Wira, Yasli; Darmawati, Darmawati; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to design a poster media based on research on theeffect of giving young coconut water on the growth of mustard greens (Brassicachinensis L) with a wick hydroponic system. This research was conducted at the NaturalLaboratory of Biology Education, Faculty of Education, Riau University in May-June2021. This research was carried out in two stages, namely the analysis and design ofposter media designs. Based on the analysis of the potential research results, it can beused as a poster media design on the growth material in Senior High School Class 12 atKD 3.1 Analyzing the relationship between internal and external factors with theprocess of growth and development in Living Things Based on Experimental Resultsand KD 4.1 Planning and carrying out experiments on factors external factors thataffect the process of plant growth and development, and report in writing using thecorrect scientific author's procedure. The design of the poster media is carried outthrough the stages of analysis and poster design consisting of the poster title,introduction, contents and bibliography.Key Words: Poster, Young Coconut Water, Mustard Plant (Brassica chinensis L), WickHydroponic System